IMPLEMENTASI NILAI TAUHID DALAM KELUARGA: MEMBENTUK KARAKTER INDIVIDU DAN MENINGKATKAN KINERJA PROFESIONAL - Heni Ani Nuraeni (Program Studi Manajemen Pendidikan Islam, 2025)
In the religious realm, the family plays a significant role in implementing religious values, including monotheism, which is one of the central concepts in Islam. Etymologically, monotheism itself means oneness. So, does the application of monotheism in the family have a positive influence on the development of individual character and their performance in an increasingly complex professional world? Therefore, this article will review how the application of the value of monotheism in the family sphere can have an impact on a person's attitude in their professional world. The approach used in this research is a descriptive qualitative approach. This research is included in primary data sources, where research data was obtained from interviews using purposive techniques. There are three techniques used by researchers in collecting research data, namely interview techniques, observation techniques, and documentation techniques. After conducting interviews, it was concluded that religious values play an important role in shaping family behavior, values, and hopes for the future. By carrying out religious practices such as prayer, reading the Koran, dressing according to the Shari'a, and praying as a way to get closer to Allah, they can form good morals in children and provide good role models